Paradoxical cerebral emboli associated with pulmonary arteriovenous shunts: report of three cases. - Desai, S P; Rees, C; Jinkins, J R (American Journal of Neuroradiology, 1991)
Paradoxical embolism to the cerebral circulation is rarely diagnosed in life; however, three such cases have recently been observed: two with multiple congenital pulmonary arteriovenous malformations and one with an acquired arteriovenous fistula. In each case the pulmonary lesion(s) were treated by percutaneous balloon embolizations. Paradoxical embolism should be included in the differential diagnosis of cerebral arterial embolism for which there is no obvious source, especially when there is also evidence of concurrent peripheral venous thrombosis and/or pulmonary embolism.